Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1177/0269215517753972
|View full text |Cite
|
Sign up to set email alerts
|

Effects and underlying mechanisms of unstable shoes on chronic low back pain: a randomized controlled trial

Abstract: This study shows that the use of unstable shoes contributes to improvements in disability, which are likely related to increased trunk muscle activity and lumbar spine ROM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 15 publications
(28 reference statements)
0
8
0
Order By: Relevance
“…Three studies used the RMDQ to evaluate the functional disability related to lower back pain. 2,7,8 Meta-analysis showed that wearing unstable shoes significantly reduced the functional disability scores of the RMDQ with a follow-up period of four to six weeks (MD −2.16, 95% CI −4.28 to −0.03; P = 0.05; I 2 = 53%) ( Figure 3).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Three studies used the RMDQ to evaluate the functional disability related to lower back pain. 2,7,8 Meta-analysis showed that wearing unstable shoes significantly reduced the functional disability scores of the RMDQ with a follow-up period of four to six weeks (MD −2.16, 95% CI −4.28 to −0.03; P = 0.05; I 2 = 53%) ( Figure 3).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 995 records were obtained from the initial database searches, and five studies 2,4,5,7,8 that met the inclusion criteria and were ultimately included after being screened and reviewed by the authors. Update search was performed in June 2019 and additional 25 records are obtained and screened.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations